2007
DOI: 10.1177/1545968307305303
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of Executive Functioning After Focal Damage to the Cerebellum

Abstract: Executive dysfunction accounts for significant disability in patients with many types of brain injury in many locations. Clinical reports have described impaired executive functioning after damage to the cerebellum, and anatomical and neuroimaging studies have identified the likely basis for this effect: a cortico-ponto-cerebellar network through which the cerebellum is densely connected to areas of frontal cortex. The patterns of executive impairment attributable to cerebellar damage have been extensively des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 24 publications
(27 reference statements)
6
38
0
Order By: Relevance
“…In general, patients reported better executive function in daily living after both treatments, whereas proxies reported a decrease in executive behavioral problems. This is in agreement with the results of previous studies, which also showed that proxies (Miotto, Evans, de Lucia, & Scaff, 2009;Schweizer et al, 2008;Spikman, Boelen, Lamberts, Brouwer, & Fasotti, 2010) and therapists (Spikman et al, 2012) reported less complaints after GMT. However, in our study post-treatment improvements were not found on all subjective cognitive measures.…”
Section: Discussionsupporting
confidence: 93%
“…In general, patients reported better executive function in daily living after both treatments, whereas proxies reported a decrease in executive behavioral problems. This is in agreement with the results of previous studies, which also showed that proxies (Miotto, Evans, de Lucia, & Scaff, 2009;Schweizer et al, 2008;Spikman, Boelen, Lamberts, Brouwer, & Fasotti, 2010) and therapists (Spikman et al, 2012) reported less complaints after GMT. However, in our study post-treatment improvements were not found on all subjective cognitive measures.…”
Section: Discussionsupporting
confidence: 93%
“…Neither study demonstrated a significant difference between the GMT group and the comparative treatment group. Nor did Schweitzer et al report a significant improvement in their case study which used the total achievement score of the D-KEFS subtest TOL [37].…”
Section: Discussionmentioning
confidence: 96%
“…Numerous neuroanatomical and neuroimaging studies have proposed the relationship between the cerebellum and executive functions (16,48,49). Cerebellum is now identified as a non-motor center playing a significant role in controlling of executive function such as language, visuo-spatial organization, emotional response, personality, reasoning, planning and sequencing (48).…”
Section: Cerebellum and Executive Functionsmentioning
confidence: 99%
“…Tasks demanding working memory activate both prefrontal cortex and cerebellum (48). Clinical reports have explained the executive dysfunction fallowed cerebellar damage (49). The classic executive dysfunctions are common and include impairments in set-shifting, planning, abstract-reasoning, verbal-fluency and working memory (16,42,53,54).…”
Section: Cerebellum and Executive Functionsmentioning
confidence: 99%
See 1 more Smart Citation